2007
DOI: 10.1177/000313480707300113
|View full text |Cite
|
Sign up to set email alerts
|

CMV Colitis Mimicking Recurrent Inflammatory Bowel Disease: Report of Three Cases

Abstract: The association between cytomegalovirus infection and inflammatory bowel disease challenges both the clinician and the pathologist to establish the correct diagnosis and to prescribe the most appropriate form of therapy. To understand this association the authors report three patients who presented with signs and symptoms mimicking reactivated inflammatory bowel disease who responded poorly to aggressive treatment of inflammatory bowel disease. Microscopic examination, in all three cases revealed numerous nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…These scattered anecdotal reports were collected in a recently published meta‐analysis 16 . A few more isolated case reports have been published lately 17–23 . Recently, we observed similar individuals, who without any obvious immunosuppressive state or previous IBD, developed colonic inflammation stemming from CMV infection.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…These scattered anecdotal reports were collected in a recently published meta‐analysis 16 . A few more isolated case reports have been published lately 17–23 . Recently, we observed similar individuals, who without any obvious immunosuppressive state or previous IBD, developed colonic inflammation stemming from CMV infection.…”
Section: Introductionmentioning
confidence: 70%
“…In this retrospective observational study, we revealed that CMV colitis is a rare occurrence but not as rare as is described in the medical literature. During a time period of 12 years we were able to collect 19 patients from our medical centre, by combining molecular virological and pathological findings, while others were able to report fewer than 50 similar patients from multiple medical facilities throughout the world in a period of 26 years (1980–2006) 16–23 …”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, severe CMV infection in immunocompetent adults often poses a significant diagnostic challenge, and a number of case reports have documented considerable delay to diagnosis 14 . ‐ 16 Some patients with CMV colitis, in particular, have had protracted hospitalisations and have undergone surgery to investigate persistent and undiagnosed disease.…”
Section: Diagnostic Challenge Of CMV Diseasementioning
confidence: 99%
“…Third, certain presentations of CMV disease strongly mimic other diseases, potentially causing diagnostic confusion and delay in diagnosis. Indeed, case studies have documented initial misdiagnoses of colon carcinoma, 14 ischaemic colitis, 15 inflammatory bowel disease, 16 dengue fever 17 and lung cancer, 18 among others.…”
Section: Diagnostic Challenge Of CMV Diseasementioning
confidence: 99%
“…17 Cobblestone-like confluent ulcers may also be seen on a pale, flattened mucosa, which can range in size from 0.7 to 2.8 cm, closely mimicking Crohn disease. 10,18 Occasionally pseudomembranes and pseudopolyps may be detected, findings that can be pitfalls in the misdiagnosis of CMV colitis as pseudomembranous colitis. 9 One study found that 11 of 44 patients with CMV colitis (25%) had normal colonic mucosa on endoscopy but histologic evidence of CMV on biopsy.…”
Section: Imaging and Gross Pathologymentioning
confidence: 99%